2020
DOI: 10.1101/2020.01.21.913814
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The photoreceptor UVR8 mediates the perception of both UV-B and UV-A wavelengths up to 350 nm of sunlight with responsivity moderated by cryptochromes

Abstract: The photoreceptors UV RESISTANCE LOCUS 8 (UVR8) and CRYPTOCHROMES 1 and 2 (CRYs) play major roles in the perception of UV-B (280–315 nm) and UV-A/blue radiation (315–500 nm), respectively. However, it is poorly understood how they function in sunlight. The roles of UVR8 and CRYs were assessed in a factorial experiment with Arabidopsis thaliana wild-type and photoreceptor mutants exposed to sunlight for 6 h or 12 h under five types of filters with cut-offs in UV and blue-light regions. Transcriptome-wide respon… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 65 publications
2
16
0
Order By: Relevance
“…Furthermore, many research groups have reported that flavonoids have a function in defense against drought, when acting as free radical scavengers (Ramakrishna & Ravishankar, 2011; Nakabayashi et al, 2014; Kumar et al, 2020). Our data is in agreement with previous research which showed that UV-B enhances accumulation of CHS transcripts, representing first committed enzyme of the flavonoid biosynthesis pathway (Brown & Jenkins, 2008; Rodríguez-Calzada et al, 2019; Rai et al,. 2020; Santin et al, 2020).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Furthermore, many research groups have reported that flavonoids have a function in defense against drought, when acting as free radical scavengers (Ramakrishna & Ravishankar, 2011; Nakabayashi et al, 2014; Kumar et al, 2020). Our data is in agreement with previous research which showed that UV-B enhances accumulation of CHS transcripts, representing first committed enzyme of the flavonoid biosynthesis pathway (Brown & Jenkins, 2008; Rodríguez-Calzada et al, 2019; Rai et al,. 2020; Santin et al, 2020).…”
Section: Discussionsupporting
confidence: 94%
“…To further study the influence of UV-B under the different treatments, we measured changes in transcript accumulation of a set of UV-B marker genes. The UV-B photoreceptor UVR8 (Jenkins, 2014) mediates responses to UV-B through interactions with specific signaling components and transcription factors which ultimately lead to the biosynthesis of phenolic compounds, such as flavonoids (Hideg, Jansen & Strid, 2013; Hideg & Strid, 2017; Jenkins, 2014; Liang, Yang & Liu, 2019; Rai et al, 2020). Transcript accumulation of UVR8 was strongly increased in UV-B-treated tobacco plants on day 14.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This research confirms that different photoreceptors trigger responses governed by UV radiation shorter than 350 nm and responses mediated by UV radiation longer than 350 nm and blue light. However, these two sets of responses interact with each other to coordinate acclimation to high light vs shade conditions [ 170 173 ]. These findings imply that perception and response to UV-B radiation not only protects against the deleterious effects of very high solar radiation but that many of these photoprotective responses can also be induced by UV-A radiation and blue light.…”
Section: Terrestrial Ecosystems and Biodiversitymentioning
confidence: 99%
“…UV-B signaling requires monomerization of UVR8, which forms a homodimer in the ground state (Rizzine et al, 2011). The absorption spectrum of UVR8 has a peak at 280 nm and extends from at least 250 nm to around 500 nm (Rai et al, 2020). Monomerization of UVR8 occurs under UV in the range from 260 to 335 nm (Díaz-Ramos et al, 2018;Rai et al, 2020).…”
Section: Introductionmentioning
confidence: 99%